Two-electron sulfonyl(trifluoromethanesulfonyl)imide-anthraquinone redox electrolytes for high-energy density supercapacitors - Yi, Zejun; Guo, De; Li, Yongsu; Liu, Lu; Dong, Shuangfei; Li, Haoxiang; Liu, Yuping; Li, Zhenhu; Liu, Shuangyi (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•Strong electron-withdrawing STFSI substitute functionalizes AQ with high stability.•AQSTFSI-K exhibits fast and highly reversible two-electron redox reactions in acetonitrile.•AQSTFSI-K shows 1.8 times specific capacitance of corresponding EDLCs.•The AQSTFSI-based ORECs display 3.2 V wide voltage, high energy density and excellent cycling stability. Organic redox electrolyte-enhanced electrochemical double layer capacitors (ORECs) are potentially better solution for combining both high power and energy density. The critical factor of ORECs is to develop high-performance organic redox electrolytes. Anthraquinone (AQ) derivatives are the promising organic redox electrolyte candidates because of their low redox potential and fast two-electron redox kinetics. Low solubility and poor longevity in aprotic solvents of charged AQ species are main issues for effective enhancement. Here we report two-electron redox ionic compounds by functionalizing AQ with a robustly electron-withdrawing sulfonyl(trifluoromethanesulfonyl)imide (AQSTFSI) anion and pairing counter monovalent cations for high-performance ORECs. The highly electron-conjugate substitute markedly stabilizes the radical and 2e−-charged forms of AQ by decentralizing the electron density of the CO heads, preventing the adverse reaction of electrophilic/nucleophilic attack, revealing by theoretical simulation. Also, the STFSI− substituent enables AQSTFSI-compounds significantly improved solubility, thermostability, and redox reversibility. Consequently, the AQSTFSI-K applied in OREC shows all-roundly superior performance containing 3.2 V cell voltage, specific energy of 58 Wh kg−1 with 1.8 times of corresponding electrochemical double layer capacitors (EDLCs), specific power over 8 kW kg−1, cycling stability over 12,000 cycles, low self-discharge, and wide working-temperature range. This molecular strategy grounded on electron density modulation of redox electrolyte structures provides valuable insights into the design for high-performance ORECs in practical applications.